Opinion Shopping dalam Audit: Tinjauan Sistematis atas Dampaknya terhadap Independensi Auditor dan Praktik Profesional - Kiky Anggrita; Rina Tjandra Kirana DP (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the practice of opinion shopping as a threat to auditor independence in issuing going concern audit opinions. This study uses a qualitative approach with a Systematic Literature Review method of 18 empirical articles indexed by Scopus and SINTA in the period 2021–2026. The analysis process was carried out through the identification, selection, and synthesis of literature to map the factors that influence the practice of opinion shopping and its implications for auditors' professional practices. The results show that financial distress is the main determinant that drives companies to engage in opinion shopping to avoid the issuance of going concern opinions. In addition, conflicts of interest between management and owners, as described in Agency Theory, also strengthen management's motivation to change auditors as a strategy to obtain more favorable audit opinions. This study also found that corporate governance mechanisms, particularly the role of the audit committee and the reputation of the Public Accounting Firm, play an important role in maintaining auditor independence from client pressure. These findings confirm that strengthening corporate governance, increasing the professional skepticism of auditors, and stricter regulatory oversight are important factors in maintaining the credibility of audit opinions and the quality of financial reporting.